1993
DOI: 10.1172/jci116501
|View full text |Cite
|
Sign up to set email alerts
|

In vivo neutralization of P-selectin protects feline heart and endothelium in myocardial ischemia and reperfusion injury.

Abstract: The cardioprotective effects of an mAb to P-selectin designated mAb PB1.3 was examined in a feline model of myocardial ischemia (MI) and reperfusion. PB1.3 (1 mg/kg), administered after 80 min of ischemia (i.e., 10 min before reperfusion), significantly attenuated myocardial necrosis compared to a nonblocking mAb (NBP1.6) for P-selectin (15±3 vs 35±3% of area at risk, P < 0.01). Moreover, endothelial release of endothelium derived relaxing factor, as assessed by relaxation to acetylcholine, was also significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
1
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(164 citation statements)
references
References 45 publications
5
156
1
2
Order By: Relevance
“…Both the superior mesenteric artery and superior mesenteric vein then were rapidly cannulated for perfusion fixation of the small bowel. The ileum was first washed free of blood by perfusion with Krebs-Henseleit buffer warmed to 37°C, bubbled with 95% O 2 and 5% CO 2 , and fixed in 4% paraformaldehyde for 90 min at 4°C as previously described (25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the superior mesenteric artery and superior mesenteric vein then were rapidly cannulated for perfusion fixation of the small bowel. The ileum was first washed free of blood by perfusion with Krebs-Henseleit buffer warmed to 37°C, bubbled with 95% O 2 and 5% CO 2 , and fixed in 4% paraformaldehyde for 90 min at 4°C as previously described (25).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical localization of P-selectin was accomplished using the avidin-biotin immunoperoxidase technique (Vectastain ABC Reagent, Vector Laboratories) as previously described by Weyrich et al (25). Positive staining was defined as a venule displaying brown reaction product on greater than 50% of the circumference of its endothelium.…”
Section: Methodsmentioning
confidence: 99%
“…It is stored in the Weibel-Palade bodies and is rapidly translocated to the endothelial surface in response to thrombin and/or oxidative stress, both of which would be likely to be found in the ischemic myocardium, and to histamine, which is rapidly released in the injured myocardium by degranulating mast cells. Experimental studies have suggested that monoclonal antibodies against L-selectin and P-selectin [183,184] reduced myocardial necrosis, preserving coronary endothelial function and attenuating neutrophil accumulation in the ischemic and reperfused feline myocardium. In addition, P-selectin deficient mice showed decreased infarct size after 30 min of coronary occlusion and 2 h of reperfusion [185].…”
Section: The Neutrophilsmentioning
confidence: 99%
“…We might speculate that patients with a higher MPV have a higher potential for platelet-leukocyte interaction and thus, are more prone to platelet-activated, leukocyte-mediated reperfusion injury. Accordingly, in experimental models, interfering with P-selectin function, which is supposed to be the key linking molecule between platelets and leukocytes, has been shown to reduce neutrophil infiltration and subsequent myocardial damage after reperfusion (29).…”
Section: Myocardial Infarction; Mpv Mean Platelet Volume; Wbc Whitmentioning
confidence: 99%